Si3N4 Nanoparticle Reinforced Si3N4 Nanofiber Aerogel for Thermal Insulation and Electromagnetic Wave Transmission - Zongwei Tong; Xiangjie Yan; Yun Liu; Yali Zhao; Kexun Li (Gels)
Traditional nanoparticle aerogels suffer from inherent brittleness and thermal instability at elevated temperatures. In recent years, ceramic nanofiber aerogels, utilizing flexible nanofibers as structural units, have emerged as mechanically resilient alternatives with ultrahigh porosity (>90%). However, their thermal insulation capabilities are compromised by micron-scale pores (10–100 μm) and overdependence on ultralow density, which exacerbates mechanical fragility. This study pioneers a gas-phase self-assembly strategy to fabricate Si3N4 nanoparticle reinforced Si3N4 nanofiber aerogels (SNP-R-SNFA) with gradient pore architectures. By leveraging methyltrimethoxysilane/vinyltriethoxysilane composite aerogel (MVa) as a reactive template, we achieved spontaneous growth of Si3N4 nanofiber films (SNP-R-SNF) featuring nanoparticle-fiber interpenetration and porosity gradients. The microstructure formation mechanism of SNP-R-SNF was analyzed using field-emission scanning electron microscopy. Layer assembly and hot-pressing composite technology were employed to prepare the SNP-R-SNFA, which showed low density (0.033 g/cm3), exceptional compression resilience, insensitive frequency dependence of dielectric properties (ε′ = 2.31–2.39, tan δ < 0.08 across 8–18 GHz). Infrared imaging displayed backside 893 °C cooler than front, demonstrating superior insulation performance. This study not only provides material solutions for integrated electromagnetic wave-transparent/thermal insulation applications but more importantly establishes an innovative paradigm for enhancing the mechanical robustness of nanofiber-based aerogels.